1996
DOI: 10.1053/jhep.1996.v23.pm0008675174
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like growth factor II/mannose 6-phosphate-receptor expression in liver and serum during acute CCl4 intoxication in the rat

Abstract: 6 While the membrane form of the receptor min immunostaining. Between 48 and 72 hours, the liver plays a role in lysosomal enzyme targeting and the gradually regained its normal appearance. As shown by promotion of cell proliferation, the role of the soluble Western blotting, in vitro differentiated FSCs released receptor remains enigmatic. It has been suggested that soluble receptor in the medium. Northern blot analysis release of soluble receptor is a mechanism of receptor showed this release to be preceded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
21
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 7 publications
(9 reference statements)
1
21
0
Order By: Relevance
“…It was reported that the level of sM6P/IGF2R in rat serum increased on liver damage. 12,19 Similarly, we found increased levels of sM6P/IGF2R in sera from patients with various liver disorders (Online Figure II), and we used these serum samples for our study.…”
Section: Interactions Of Sm6p/igf2r With Plgmentioning
confidence: 83%
“…It was reported that the level of sM6P/IGF2R in rat serum increased on liver damage. 12,19 Similarly, we found increased levels of sM6P/IGF2R in sera from patients with various liver disorders (Online Figure II), and we used these serum samples for our study.…”
Section: Interactions Of Sm6p/igf2r With Plgmentioning
confidence: 83%
“…The M6P/IGFIIR protein was found in rat stellate cells in vivo by 48 h after administration of carbon tetrachloride (CCl 4 ) (13), a potent inducer of hepatic fibrogenesis. The M6P/IGFIIR transcript was previously found to be undetectable via Northern analysis in normal (quiescent) stellate cells (13). In whole liver RNA, the M6P/IGFIIR transcript level peaked at 48 h after CCl 4 treatment (13).…”
mentioning
confidence: 97%
“…Therefore, conjugating very potent inhibitors of cell proliferation to the HSC-selective drug carrier mannose-6-phosphate-modified human serum albumin (M6PHSA) has now become an option. M6PHSA has been shown to accumulate in HSC in vivo via binding to mannose-6-phosphate/insulin-like growth factor-II receptors that are up-regulated on the cell surface of activated HSC (de Bleser et al, 1995(de Bleser et al, , 1996Beljaars et al, 1999). Ligands bound to the receptor are subject to receptor-mediated endocytosis and are routed to the acidic lysosomal compartment, where degradation of the construct and subsequent release of the coupled drug may take place (Braulke and Mieskes, 1992;Dahms and Hancock, 2002).…”
mentioning
confidence: 99%